Spiritual well-being among patients with chronic illness - Ranron, Thammawit; Khitka, Pornsawan; Jaimalai, Wichanee; Tangsutthitham, Traichadchaya (Journal of The Royal Thai Army Nurses, 2021)
Living with chronic illness affects patients’ spiritual health. Spiritual well-being helps patients maintain their psychological balance, understand self and nature of life, have sense of connectedness, and have hope of living by the way of Buddhism. This descriptive study aimed to investigate spiritual well-being among patients with chronic illness. 394 persons with chronic illness residing in Muang District, Phayao Province were recruited using simple random sampling. Data were analyzed using by descriptive statistics. The results of the study revealed that the majority of participants had high levels of total spiritual well-being (89.6%); peacefulness (91.1%), having hope and sense of connectedness (82.0%), and understanding of self and life nature (81.7%), respectively The results of this study can be fundamental information for health care providers to enhance spiritual well-being in chronically ill patients through the way of Buddhism. This might help patients live with their illness happily and have a good quality of life ultimately